TINDAK TUTUR DIREKTIF PEGAWAI KELURAHAN DALAM PELAYANAN MASYARAKAT DI KELURAHAN TAMALANREA INDAH KOTA MAKASSAR - IAN WAHYUNI,; MUHAMMAD DARWIS,; IKHWAN M SAID, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The positive impact of excellent service that is evenly distributed at all levels of society in the village office is the inculcation of moral values ??and benchmarks of public services. This study aims to reveal the form of politeness directive speech acts of village employees in community service at the Tamalanrea Indah Village Office. This type of research is a qualitative description with a natural phenomenon description method. Data source, namely communication between village officials and the community in the Tamalanrea Indah Village Office. Data collection is done by listening and interviewing methods, as well as listening, recording and interview techniques. The results showed that there were six forms of politeness in directive speech act of village employees. The highest politeness level is found in the supplication form because the imperative element of the speaker is disguised. The lowest politeness level is found in the ordered form because most direct speech acts are used, so the imperative element is very clear.